Seismic behavior of transfer girder in multi-story building - Guptaa, Samrat; R. Kannanra jkumar, P; T. Ravichandran, P; Krishnaraj, L (International Journal of Engineering and Technology, 2018)
Urbanization had led to many housing problems in India. Scarcity of land is one such biggest problem in India. This issue is one of the most pivotal issues that need to be provided with a swift and efficient solution if we want to grow as a nation whilst achieving the goals we are aiming at. Hence, there is a rise in many Multi storey and Highrise structure. Rise in car park and open column free space for auditoriums. The study focuses on the study of seismic assessment of the Multi-storey structure with transfer girder. The use of transfer girders in a building will help to a greater extent to minimize the issue regarding the lack of space for car parking. A building prototype model with transfer girder at different level was analyzed using elastic linear response spectrum. Different results such as Base Shear, Time Period, Interstorey Drift and Displacement had been analysed in different model and optimum modeling of Multi storey RC Frame building with transfer girder system using SAP 2000 and also comparison on performance of Multi storey building by placing the transfer girder in different level has been carried out.